Análise da relação entre crescimento econômico e desmatamento baseado na hipó- tese da curva de Kuznets ambiental para a Amazônia Legal no início do terceiro milênio - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
In recent years, the warning about environmental degradation have been gaining prominence in the news and on global political agendas. In the case of Brazil, attention has been focused mainly on the Legal Amazon, considered the largest tropical forest in the world. Thus, deforestation in this region presents a serious threat to biodiversity and the provision of environmental services, essential for maintaining global climate conditions. In this sense, the present study aims to understand, through the Environmental Kuznets Curve theory - EKC, the impacts of economic growth on deforestation in the Legal Amazon from 2002 to 2020. After a bibliographic survey of works that address the relationship between income growth and environmental degradation for the Legal Amazon and the collection of data with information on GDP per capita - proxy for economic growth (obtained from the SIDRA-IBGE website) and three proxies for environmental degradation - Deforestation rate (km2), Accumulated deforestation and Annual increase in deforestation (obtained from the PRODES-INPE website), a polynomial regression model with panel data was then applied to estimate three Environmental Kuznets Curves for the states that make up the Legal Amazon. After estimating and applying the tests to select the model, the result obtained was a normal “U” shape in the cubic function – with fixed effects, both for the relationship between GDP per capita and Deforestation Rate (km2), and for the relationship between GDP per capita and Annual Deforestation Increase, and an inverted “N” shape in the quadratic function – with fixed effects, for the relationship between GDP per capita and Accumulated Deforestation. The results obtained show EKC shapes that are different from those proposed by theory, demonstrating, based on the literature review, that there is no standard EKC shape for the Legal Amazon, indicating that there are limitations to the EKC theory in explaining the relationship between economic growth and environmental degradation.
Keywords: Crescimento Econômico; Degradação Ambiental; Curva de Kuznets Ambiental; Amazônia Legal Brasileira; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS